Correlation between photoluminescence and structural defects in Ca 1+x Cu 3 - X Ti 4 O 12 systems - Oliveira, Larissa H.; Paris, Elaine C.; Avansi, Waldir [UNESP]; Ramirez, Miguel A. [UNESP]; Mastelaro, Valmor R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley, 2013)
Ca1+xCu3-xTi4O12 powders were synthesized by a conventional solid-state reaction. X-ray diffraction (XRD) was performed to verify the formation of cubic CaCu3Ti4O 12 (CCTO) and orthorhombic CaTiO3 (CTO) phases at long range. Rietveld refinements indicate that excess Ca atoms added to the Ca 1-xCu3-xTi4O12 (x = 1.0) composition segregated in a CaTiO3 secondary phase suggesting that solubility limit of Ca atoms in the CaCu3Ti4O12 lattice was reached for this system. The FE-SEM images show that the Ca 1+xCu3-xTi4O12 (0 < x < 3) powders are composed of several agglomerated particles with irregular morphology. X-ray absorption near-edge structure spectroscopy (XANES) spectra indicated [TiO5Vo z]-[TiO6] complex clusters in the CaCu3Ti4O12 structure which can be associated with oxygen vacancies (Vo z = V o x, Vo •, and Vo ••) whereas in the CaTiO3 powder, this analysis indicated [TiO6]-[TiO6] complex clusters in the structure. Ultraviolet-visible (UV-vis) spectra and photoluminescence (PL) measurements for the analyzed systems revealed structural defects such as oxygen vacancies, distortions, and/or strains in CaCu3Ti4O12 and CaTiO3 lattices, respectively. © 2012 The American Ceramic Society.
Keywords: Agglomerated particles; Complex clusters; Irregular morphology; Long range; Photoluminescence measurements; Secondary phase; Solubility limits; Structural defect; TiO; Ultraviolet-visible spectra; Oxygen vacancies; Photoluminescence; Powders; Rietveld refinement; Solid state reactions; X ray diffraction; Calcium